Technological Pedagogical Content Knowledge (TPACK) in Physical Education Teacher Education (PETE): A Systematic Scoping Review - Wang, Jianxun; Samsudin, Shamsulariffin; Hidayat, Riyan (Routledge, 2026)
The purpose of this systematic review is to identify and analyze the peer-reviewed literature on the technological pedagogical content knowledge (TPACK) in physical education teacher education (PETE) from 2012 to 2024. We analyzed 10 articles that met the inclusion criteria of three databases. This study has followed systematic review guidelines. The results of this systematic review indicate that empirical research on TPACK within PETE remains insufficient. Existing studies rely heavily on quantitative methods and are concentrated in a limited number of geographic regions. Research on TPACK in PETE is limited and constrained in terms of methodology, it highlights the value of the framework in developing digitally competent of PETE. Future research should focus on exploring how to apply TPACK framework in practice to enhance its theoretical and practical impact, while also expanding the geographical scope of research.